2011
DOI: 10.1021/ac202646v
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and Characterizing Skin Ceramides Using Reversed-Phase Liquid Chromatography–Quadrupole Time-of-Flight Mass Spectrometry

Abstract: An LC-MS based method for the profiling and characterization of ceramide species in the upper layer of human skin is described. Ceramide samples, collected by tape stripping of human skin, were analyzed by reversed-phase liquid chromatography coupled to high-resolution quadrupole time-of-flight mass spectrometry operated in both positive and negative electrospray ionization mode. All known classes of ceramides could be measured in a repeatable manner. Furthermore, the data set showed several undiscovered ceram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
166
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(180 citation statements)
references
References 34 publications
11
166
0
3
Order By: Relevance
“…These unusual ultra-long chain lipids were first documented in meibomian gland secretions just over a decade ago (8), but have since been detected in skin (5), equine sperm (6) and amniotic fluid (7), and as components of complex lipids such as cholesteryl esters in meibum (14) and vernix caseosa (15), and acylceramides in the skin (i.e., esterified ω-hydroxyacyl-sphingosine) (5,(16)(17)(18). Since their first detection, the assignation of the hydroxy ester at the terminal (ω-) position has largely resulted from early work using saponified meibum extractions (38); however, the more recent discovery of FAHFA with multiple ester substitution positions has necessitated clarification of OAHFA structure.…”
Section: Discussionmentioning
confidence: 99%
“…These unusual ultra-long chain lipids were first documented in meibomian gland secretions just over a decade ago (8), but have since been detected in skin (5), equine sperm (6) and amniotic fluid (7), and as components of complex lipids such as cholesteryl esters in meibum (14) and vernix caseosa (15), and acylceramides in the skin (i.e., esterified ω-hydroxyacyl-sphingosine) (5,(16)(17)(18). Since their first detection, the assignation of the hydroxy ester at the terminal (ω-) position has largely resulted from early work using saponified meibum extractions (38); however, the more recent discovery of FAHFA with multiple ester substitution positions has necessitated clarification of OAHFA structure.…”
Section: Discussionmentioning
confidence: 99%
“…UPLC-coupled tandem mass spectrometric analyses revealed that 1-Oacylceramides are present at 280 ± 70 fmol per pmol of NS-Cers. The latter represent about 7.4% of all Cers in human stratum corneum ( 30 ). In humans, 1-O-lignoceroyl Cer(d18:1; h16:0) was the most prominent peak, followed by 1-O-palmitoyl Cer(d18:1;16:0) and 1-O-palmitoyl Cer(d18:1;h16:0) ( Fig.…”
Section: -O-acylceramides Are Present In Human Stratum Corneummentioning
confidence: 92%
“…Besides, efforts have been made, by applying mild alkaline hydrolysis [16,18,19,23,32], or solid phase extraction (SPE) [20,33], aimed at reduced ion suppression, especially in a shotgun pattern. Nevertheless, these methods were hampered either by limited throughput in using SPE, or by inconstant factors of dripping loss or possible interfering protein in using chloroform/methanol/water.…”
Section: Serum Sphingolipid Extractionmentioning
confidence: 99%